2017
DOI: 10.21037/jtd.2017.03.148
|View full text |Cite
|
Sign up to set email alerts
|

The safety profile of preoperative administration of heparin for thromboprophylaxis in Chinese patients intended for thoracoscopic major thoracic surgery: a pilot randomized controlled study

Abstract: NCT02940444 (https://register.clinicaltrials.gov/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…A significant difference has been detected at the time of the first dose usage preoperatively, but no clue on postoperative patients. A literature (18) demonstrated that it is safe and feasible to take preoperative use of heparin for thromboprophylaxis in Chinese patients. However, due to the usage risks of heparin, the timing of anticoagulation is important.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference has been detected at the time of the first dose usage preoperatively, but no clue on postoperative patients. A literature (18) demonstrated that it is safe and feasible to take preoperative use of heparin for thromboprophylaxis in Chinese patients. However, due to the usage risks of heparin, the timing of anticoagulation is important.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, almost patients had no major postoperative complications such as severe pulmonary infection and bronchopleural fistula, except one patient who underwent esophagectomy suffered anastomosis leakage and secondary pulmonary infection. Chest drainage tube duration (days) 4.22 [1][2][3][4][5][6][7][8][9][10] Treated with conservative therapies including mixed nutrition of enteral and parenteral alimentation, thoracic cavity drainage, anti-infection, electrolyte balance and other symptomatic treatments, the patient recovered well and discharged with stable vital signs and ability to have half-fluid food. Another one experienced right pneumothorax when the chest drainage tube was removed, then chest drainage tube was administrated again until the symptoms disappeared and the DR image of chest showed well.…”
Section: Resultsmentioning
confidence: 99%
“…The development of VTE is associated with surgery, malignant cancers, age, immobilization, obesity, history of VTE, infection, radiotherapy (1,4). So there is no doubt that the patients diagnosed with malignant neoplasm have a higher risk suffering VTE, especially those with surgical resection (5). Cancer patients were reported to have around 5-to 7-fold higher risk of VTE compared with normal population (6).…”
Section: Introductionmentioning
confidence: 99%
“…Thromboprophylaxis often starts postoperatively in thoracic surgical patients (21). Deng et al recommended preoperative DVT prophylaxis with heparin in patients intended for major thoracic surgery (22). DVT may develop during surgery due to venous stasis and the release of thrombogenic substances from lung tissue (8).…”
Section: Discussionmentioning
confidence: 99%